Oisko linnun lentoneuot : Kantelettaren runo ja taustavaikutteiden verkosto - Kallio, Kati (Suomalaisen Kirjallisuuden Seura, 2021)
The article analyses one poem, compiled by Elias Lönnrot for the lyrical collection Kanteletar (1949). Using Octavo interface by Eetu Mäkelä, the article tests the possibilities of comparative digital reading on extremely varying corpus of historical oral poetry. In the analysis, the earlier manual interpretations by Väinö Kaukonen on the working process of Lönnrot and the folklore materials he used are validated and added. It becomes evident that, in this case, Lönnrot not only made use of rich corpus of Finnic oral poetry in Kalevala-meter, but also of Viena Karelian joik, itself a hybrid genre mixing lament-like free verse and Kalevala meter. In addition, Lönnrot seems to have been taking influences from the famous 17th century poem by Kemi Saami Olaus Sirma. Peer reviewed